2014
DOI: 10.1016/j.jsat.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Deriving costs of service use among an urban homeless population

Abstract: The purpose of this study was to describe a novel approach to calculating service use costs across multiple domains of service for homeless populations. A randomly-selected sample of homeless persons was interviewed in St. Louis, MO and followed for two years. Service- and cost-related data were collected from homeless individuals and from the agencies serving them. Detailed interviews of study participants and of agency personnel in specific domains of service (medical, psychiatric, substance abuse, homeless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…In addition, there is no consensus on how attaining housing affects service use costs. In contrast to our research (7,8), Larimer and colleagues (3) found that attaining housing was associated with reduced medical care costs.…”
contrasting
confidence: 96%
See 4 more Smart Citations
“…In addition, there is no consensus on how attaining housing affects service use costs. In contrast to our research (7,8), Larimer and colleagues (3) found that attaining housing was associated with reduced medical care costs.…”
contrasting
confidence: 96%
“…Details about the baseline characteristics of this sample of 255 homeless individuals have been previously reported (5,8). To summarize, the sample was predominantly African American (N=192, 75%) and male (N=187, 73%), with a high school education on average (N=149 of 249 participants; 60%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations